Loss and Recovery of Glutaredoxin 5 Is Inducible by Diet in a Murine Model of Diabesity and Mediated by Free Fatty Acids In Vitro - Sebastian Friedrich Petry; Axel Römer; Divya Rawat; Lara Brunner; Nina Lerch; Mengmeng Zhou; Rekha Grewal; Fatemeh Sharifpanah; Heinrich Sauer; Gunter Peter Eckert; Thomas Linn (MDPI AG, 2022)
Free fatty acids (FFA), hyperglycemia, and inflammatory cytokines are major mediators of β-cell toxicity in type 2 diabetes mellitus, impairing mitochondrial metabolism. Glutaredoxin 5 (Glrx5) is a mitochondrial protein involved in the assembly of iron-sulfur clusters required for complexes of the respiratory chain. We have provided evidence that islet cells are deprived of Glrx5, correlating with impaired insulin secretion during diabetes in genetically obese mice. In this study, we induced diabesity in C57BL/6J mice in vivo by feeding the mice a high-fat diet (HFD) and modelled the diabetic metabolism in MIN6 cells through exposure to FFA, glucose, or inflammatory cytokines in vitro. qRT-PCR, ELISA, immunohisto-/cytochemistry, bioluminescence, and respirometry were employed to study Glrx5, insulin secretion, and mitochondrial biomarkers. The HFD induced a depletion of islet Glrx5 concomitant with an obese phenotype, elevated FFA in serum and reactive oxygen species in islets, and impaired glucose tolerance. Exposure of MIN6 cells to FFA led to a loss of Glrx5 in vitro. The FFA-induced depletion of Glrx5 coincided with significantly altered mitochondrial biomarkers. In summary, we provide evidence that Glrx5 is regulated by FFA in type 2 diabetes mellitus and is linked to mitochondrial dysfunction and blunted insulin secretion.